EFEKTIFITAS KOMUNIKASI GRU DENGAN MOTIVASI BELAJAR SISWA SEKOLAH MENENGAH ATAS NEGERI - Siti Khadijah; Galih Dwi Martanto (Fakultas Komunikasi, Sastra, dan Bahasa, 2017)
Teachers should understand about the motivation of study towards their students, it is important to keep and raise their motivations. Because teachers as a motivator of their students in the school, therefore they should be able to raise their students motivation in study. As the ability of teachers in SMAN 1 Cibitung in the way of motivate their students to study by the communication process. However from 56 teachers there are only some of them who can motivate their students. This research purposes are to know how much effective the teacher’s communication in study process and to understand about teacher’s communication when they build their student motivation in SMAN 1 Cibitung